Ethical considerations of AI in financial decision - Wang, Yifei (Computing and Artificial Intelligence, 2024)
The integration of artificial intelligence (AI) in financial decision-making processes has significantly enhanced the efficiency and scope of services in the finance sector. However, the rapid adoption of AI technologies raises complex ethical questions that need thorough examination. This paper explores the ethical challenges posed by AI in finance, including issues related to bias and fairness, transparency and explainability, accountability, and privacy. These challenges are scrutinized within the framework of current regulatory and ethical guidelines such as the General Data Protection Regulation (GDPR) and the Fair Lending Laws in the United States. Despite these frameworks, gaps remain that could potentially compromise the equity and integrity of financial services. The paper proposes enhancements to existing ethical frameworks and introduces new recommendations for ensuring that AI technologies foster ethical financial practices. By emphasizing a proactive approach to ethical considerations, this study aims to contribute to the ongoing discourse on maintaining trust and integrity in AI-driven financial decisions, ultimately proposing a pathway towards more robust and ethical AI applications in finance.